Determining factors of game performance in the 2001 water polo championships - Takagi, H.; Nishijima, T.; Enomoto, I.; Stewart, A. M. (Journal of Human Movement Studies, 2005)
The purposes of the present study were to clarify how water polo is played at an international level and to investigate the relationship between game performance and skill components of world-class water polo players. The 9th FINA World S wimming Championships of Water Polo for men and women 2001 was chosen for analysis. In total, there were 60 matches for men, and 48 matches for women, each match produced data for two teams and thus provided the potential for the analysis of 216 team perforniances. An original database program designed specifically for water polo match analysis was developed and data were input irnmediately whenever an event happened during a match. In order to obtain an overall picture of game performance for our study. we selected 21 items for offense and 11 items for defense. Principal component analysis and varimax rotation were used to determine the factorial structure of the garne performance. Ten common factors were extracted. which accounted for 83% of the total variance in the 32 variables. The results of present study indicated two key areas th a t determine theoutcomeof a game. First, the ability to counterattack impacts on winning or losing. Top-ranked teams more often than not convert their chances to score when up an extraman. Low-ranked teams often fail to score when playing with superior numbers. Second, the ability to defend when down a player impacts substantially on the outcome. The better teams are more successful in producing a blocked or saved shot.